The Role of Organizational Justice Perceived by Teachers on the Ethical Dilemmas They Experience - Esra Saçlı; Fatih Camadan (Uluslararası Türk Eğitim Bilimleri Dergisi)
This study aims to examine the role of organizational justice perceived by teachers in the ethical dilemmas they experience. The research, conducted using a correlation survey model, included a sample of 379 teachers (215 female and 164 male) working in secondary and high schools. The findings of the research revealed that there were no significant differences in the ethical dilemmas experienced by teachers based on variables such as gender, age, type of institution, and education level. However, it was found that there was a significant difference in the behavioral ethical dilemma dimension, structural ethical dilemma dimension, and the overall score of ethical dilemmas at schools based on the teachers' branch of specialization. Furthermore, differences were identified in the structural ethical dilemma dimension based on the type of employment. In addition, the study revealed that there was a negative, low-level, and significant relationship between teachers' ethical dilemma levels and their perceptions of organizational justice. Organizational justice was found to predict 8% of the total variation in ethical dilemmas. Moreover, the behavioral ethical dilemma dimension was found to significantly contribute to the total score of ethical dilemmas in schools. However, the structural ethical dilemma dimension and the interactional ethical dilemma dimension did not significantly contribute to the overall score of ethical dilemmas in schools.